EKSISTENSI BALAI PEMASYARAKATAN DALAM SISTEM PERADILAN PIDANA ANAK (Studi Pada Balai Pemasyarakatan Kelas II Bukittinggi) - Maisa, Aditya (UNES Journal of Swara Justisia, 2018)
The State has an obligation to fulfill the rights of children in conflict with the law, both children as perpetrators, victims, or witnesses. Prisons have an important role in assisting children who are in conflict with the law inside and outside the criminal justice process.Based on Background above, the writer formulates the problem as follows: 1. How is Existence of Correctional Institution in Child Criminal Justice System? 2. What are the obstacles faced by the Bukittinggi Class II Prison in guiding the child facing the law, and how to overcome these obstacles?The research method used in this thesis research is with analytical descriptive research specification. In this research, the approach used is juridical approach method. This approach is also supported by an empirical juridical approach, by looking at how legislation is applied in practice in the field. The data source that writer use is secondary data and primary data. The data obtained were analyzed qualitatively and presented in the form of descriptive analysis. Based on the results of research and discussion, it can be concluded that the existence of the Central Penitentiary in the Child Criminal Justice System is very important. In performing its duties and functions, the Penal Institution also faces various obstacles including, the rule of law, coordination, low quality of human resources, lack of facilities and infrastructure, wide working area, client family factor, and limited budget allocation.